Integrated Antenna Design with SAW Filters - Saranya , K. R.; Kalaiyarasi , D.; Sugumar, D.; J, Jeba Johannah; Dhivya , S.; Kunisetti , Subramanyam; Thilagavathy, A.; Satyanarayana , T. V. V. ‎ (International Journal of Basic and Applied Sciences, 2025)
This work presents the design, simulation, and fabrication of a branch-and-leaf fractal Antipodal Vivaldi antenna, demonstrating a 60% size ‎reduction compared to a conventional counterpart. Despite a 15% decrease in radiation characteristics, the antenna satisfies the ultra-‎wideband (UWB) requirements essential for applications such as ground-penetrating radar (GPR) systems used in humanitarian demining ‎in Colombia. The enhanced performance is attributed to the additional resonant modes introduced by the fractal geometry, which increases ‎gain across multiple frequencies. The resulting miniaturization facilitates a reduced form factor for GPR systems, improving field deploy-‎ment and operational efficiency. Future work includes a parametric study of alternative fractal geometries, such as Minkowski Island ‎designs, to further optimize performance and integration into advanced field measurement systems for sustained demining operations‎.